2002
DOI: 10.1177/0044118x02034001001
|View full text |Cite
|
Sign up to set email alerts
|

Moral Panic Over Youth Violence

Abstract: In 1989, while reporting the well-publicized attack on a female jogger in New York City, the media discovered wilding, a newly stylized word used to describe sexual violence committed by a group of urban teens. Sociologically, the term wilding became particularly significant due to its racial connotation, perpetuating a stereotype of young Black (and Latino) males belonging to a dangerous class. This work explores the contours of moral panic over wilding by attending to elements of race, class, and fear of cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition and contrarily to the broadsheet newspaper, in the Bild personification ("individualism" according to Jewkes 2011) may be a news factor of great importance, too, because of the attribution of individual causation. Youth and immigration in combination result in crime is the message of the tabloid, demonizing young immigrants as the "criminal other" (Greer 2007:36; see also, e.g., Greer and Jewkes 2005;Humphries 1981;Jewkes 2004;Schissel 1991;Welch, Price, and Yankey 2002). Following such clear thought patterns also implies the importance of clear and distinct courses of events and consequences in the Bild, and might also underline the political desire of the Bild's journalists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition and contrarily to the broadsheet newspaper, in the Bild personification ("individualism" according to Jewkes 2011) may be a news factor of great importance, too, because of the attribution of individual causation. Youth and immigration in combination result in crime is the message of the tabloid, demonizing young immigrants as the "criminal other" (Greer 2007:36; see also, e.g., Greer and Jewkes 2005;Humphries 1981;Jewkes 2004;Schissel 1991;Welch, Price, and Yankey 2002). Following such clear thought patterns also implies the importance of clear and distinct courses of events and consequences in the Bild, and might also underline the political desire of the Bild's journalists.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of a moral panic was examined by Welch, Price, and Yankey (2002). They showed that, after an attack on a New York Central Park jogger, "wilding" was greatly exaggerated in the media and "emerged as a symbolic expression of anxiety over youth violence resulting in young men of color being scapegoated as villains, folk devils, and other representations of evil" (22).…”
Section: What Is Media Crime?mentioning
confidence: 99%
“…This causes the stigma to end up falling on larger groups through the construction of a common imaginary which surrounds the young male and female members of groups and forms the basis of the aforementioned 'gang problem' (Zatz, 1987). These representations clearly help to build and promote moral panic (Zatz, 1987) which ends up justifying law and order campaigns and measures (Welch, Price and Yankey, 2002;Queirolo Palmas, 2017).…”
Section: Street Youth Groups Violence and Moral Panicmentioning
confidence: 99%
“…At such times, any potential firewalls between public policies and such sensationalized, culturally constructed discourses of bias collapse. Laws are passed and policies enacted that create coercive forms of control, further scapegoating the unpopular group (Langton & DuRose, 2013;Welch et al, 2002).…”
Section: The Learning Landscapementioning
confidence: 99%